Computer-dependent or computer-assisted?: the social context of online crime in Lithuanian court judgements - Šupa, Maryja (International journal of law, crime and justice, 2023)
This paper addresses the relative lack of studies concerning characterisation of online crime in court judgements. The goal was to outline the social context of computer-dependent online offences in Lithuania as enacted in court practice. It is an internationally relevant example of the applied outcomes of local legislation enacting the Budapest Convention on Cybercrime. We focused on four key themes to explore how computer-dependent online crime was defined in court practice: offences, offenders, victims, and sentences, bound by the concept of selectivity in criminal justice. A mixed-methods approach was utilised to analyse 265 court judgements in online offence cases in Lithuania from the years 2017-2021. The results revealed that the majority of the offences were computer-enabled rather than computer-dependent, carried out by persons with previous experience in the criminal justice system seeking financial gain.